Belonging in the Mix - Liz Przybylski (Muzikološki Zbornik)
Whose sounds fit in the nation-state? Countering histories of erasure, this essay investigates the role of hip hop music in articulating Black and Native histories and presence in Canada. Analysis of music by Kardinal Offishall, Webster, and Winnipeg’s Most demonstrates how minority and Indigenous groups express belonging and sovereignty, respectively.